Role of High Power Laser Therapy on Pain Reduction in Patients with Patellofemoral Pain Syndrome - Hafiz Ammar Qayyum, Syed Asadullah Arsalan, Fahad Tanveer, Ashfaq Ahmad, Javaria, Syed Amir Gilani, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Patellofemoral pain syndrome also known as chondromalacia patella is a very common musculoskeletal disorder in adolescents and athletes. The underlying cause of PFPS is unknown, but some medical experts believe that pain in the knee area is caused by other soft tissue, muscular, and biomechanical abnormalities. If PFPS is not treated in a controlled manner, then it can cause quadriceps muscle weakness. PFPS affects both adults and teens with a prevalence rate of 23% for most people. The prevalence of PFPS is higher for women compared to men. Usually, the diagnosis of PFPS is slow because there is a cluster of signs and symptoms. Aim: To determine the effects of high power laser therapy on pain reduction in patients with patellofemoral pain syndrome. Methodology: It is a RCT (randomized controlled trial). There were two groups i.e. Control group (routine physiotherapy) and treatment group(routine physiotherapy + Hi power laser therapy) with 33 patients in each group (total of 66 participants of study). VAS scoring was used to interpret the data. The data was analyzed statistically and then was compared to study the difference between two groups. Results: The data was statistically analyzed and showed the difference between two groups of the study. The value of P is less than 0.05 which was considered significant. Conclusion: It is concluded that the patients who receive HPLT (high power laser therapy) along with routine physiotherapy showed better results and progress in pain reduction than those who only receive routine physiotherapy treatment.